A comparison of brief and extended session duration functional analyses. Issue 3 (17th March 2021) - Griffith, Lee S.; Roscoe, Eileen M.; Cornaglia, R. Benjamin
Abstract : Many behavior analysts do not conduct a functional analysis (FA) prior to treatment in a clinical setting (e.g., Roscoe et al.,  2015). When asked for an explanation, respondents commonly report that an FA is too time consuming. One way to address this perceived constraint is to evaluate the utility of an abbreviated FA with 5‐min session durations. In the current study, 2 independent FAs, 1 with 5‐min sessions and 1 with 10‐min sessions, were conducted for the problem behavior of 5 individuals diagnosed with autism spectrum disorder (ASD). For all participants, the 5‐ and 10‐min session duration FAs yielded the same identified function of problem behavior: escape from demands. A brief differential reinforcement of alternative behavior (DRA) analysis was subsequently conducted and found to be effective at decreasing problem behavior and increasing an appropriate communication response across participants. These findings demonstrate the utility of conducting an FA using briefer session durations followed by a brief DRA analysis.